Reflection Crack Analysis of Asphalt Overlay on Cement Concrete Pavement Based on XFEM - Qiang Li; Zhixiang Chen; Shaohui Luo (Advances in Civil Engineering)
Based on the improved Paris formula, the reflection cracking characteristics of asphalt overlay on the cement concrete pavement are carefully scrutinized. The fatigue life is also predicted through the indoor simulation tests and establishing the two- and three-dimensional extended finite-element method (XFEM) models. Four fracture factors of the Paris formula in the asphalt mixture are appropriately calculated by fitting the N-a curve of the indoor test, and their predicted values are then exploited in the numerical simulations. The obtained results show that the numerical model can successfully predict the results of the indoor simulation test. It indicates that the XFEM has apparent advantages in examining the reflection cracking of the asphalt overlay on the cement concrete pavement.